Flightplan - Schwentke, Robert, 1968-; Foster, Jodie; Sarsgaard, Peter; Christensen, Erika, 1982-; Bean, Sean; Lawston, Marlene; Ballhaus, Florian, 1965-; Horner, James; Touchstone Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, CA : Touchstone Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
Flying at 40,000 feet in a cavernous, state-of-the-art 474 aircraft that she designed, Kyle Pratt faces every mother's worst nightmare when her six year-old daughter, Julia, vanishes without a trace mid-flight from Berlin to New York
English track: Dolby digital 5.1; DTS 5.1
French track: Dolby digital 5.1
Spanish track: Dolby digital 5.1
Title from container
Originally released as a motion picture in 2005
Special features: 'The in-flight movie : the making of Flightplan' featurette; 'Cabin pressure : designing the Aalto E-474' featurette; filmmaker audio commentary
Keywords: Mothers of kidnapped children -- Drama; Flight crews -- Drama; Air pilots -- Drama; Feature films; Films for the hearing impaired